Aversion to Breaking Rules and Migration - Massimo Anelli; Tommaso Colussi; Andrea Ichino (Institute of Labor Economics (IZA), 2021)
Migration movements may increase the geographic dispersion of the Aversion to Breaking Rules (ABR) in a population, with possible long-term economic consequences. We show this result with Italian Census data, using indicators of false birth date registrations for families of South-North migrants and remainers in the two macro-regions. Within localitybiennium cells, deterrence and cheating benefits are similar in the two groups and thus cheating differences are informative about the underlying ABR, as our theory suggests. We also exploit the Fascist reforms of 1926 as shocks to deterrence, offering additional information on the underlying ABR of migrant and remainer families.
Keywords: J61; C93; R23; 330; migration; aversion to breaking rules; Italy